Edukasi Gizi MP-ASI Sebagai Alternatif Pencegahan Stunting - Lolita A.M. Parera; I Gusti M.N Budiana; Yantus A.B. Neolaka; Jasman Jasman; Kasimir Sarifudin; Ni Wayan O.A.C. Dewi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Nutritional problems occur in various forms, such as thin children (wasting), short children (stunting), and children who are overweight. The most nutritional problem that occurs in children is stunting at 23.8%. Nutrition education is important to improve eating habits and correct food choices. Providing nutrition education can not only increase knowledge but can also change health behavior. Providing education is also provided for handling and preventing stunting. East Nusa Tenggara has a fairly high stunting rate. Therefore, currently the Kupang Regency government is aggressively implementing various programs to reduce stunting rates. Efforts to prevent cases of stunting can be done through providing MP-ASI intake for babies and toddlers as well as changing lifestyle patterns. In fact, partners' knowledge about MP-ASI nutrition which can prevent stunting is very minimal. Residents also have minimal information regarding the processing of nutritious MP-ASI. The solution offered to partners is to provide education about MP-ASI nutrition to prevent stunting, the characteristics of toddlers who experience stunting, short and long term impacts, and how to handle stunting cases, the benefits of MP-ASI and processing nutritious MP-ASI for babies. and child